2021
DOI: 10.1089/gtmb.2020.0166
|View full text |Cite
|
Sign up to set email alerts
|

E2F5 Promotes the Malignancy of Ovarian Cancer Via the Regulation of Hippo and Wnt Pathways

Abstract: Background: E2F5 is a transcription factor that is overexpressed in the early stages of ovarian cancer and has been suggested as a potential biomarker for early detection. In this study, we aimed to examine the role of E2F5 in invasion and proliferation of ovarian cancer cells. Materials and Methods: We performed cell viability, colony formation, and invasion assays using ovarian cancer cells treated with siRNA to knock down the E2F5 gene. The regulatory effects of E2F5 on proteins involved in the apoptotic, W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…41 E2F5, which was highly expressed in malignant tissues when compared to the nonmalignant tissues, promoted ovarian carcinogenesis by regulating Hippo and Wnt pathways. 42 In this research, we showed that the expression of E2F5 in normal tissues was higher than that in kidney cancer tissues, but that there was no differential mRNA expression of E2F5 in ccRCC cell lines. According to the E2F5 expression in normal tissues compared with cancer tissues, it might play an inhibitory role, but a higher E2F5 expression showed a significant association with poor OS.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…41 E2F5, which was highly expressed in malignant tissues when compared to the nonmalignant tissues, promoted ovarian carcinogenesis by regulating Hippo and Wnt pathways. 42 In this research, we showed that the expression of E2F5 in normal tissues was higher than that in kidney cancer tissues, but that there was no differential mRNA expression of E2F5 in ccRCC cell lines. According to the E2F5 expression in normal tissues compared with cancer tissues, it might play an inhibitory role, but a higher E2F5 expression showed a significant association with poor OS.…”
Section: Discussionmentioning
confidence: 66%
“…E2F5 was aberrantly overexpressed in several tumors, such as breast tumor, 41 and ovarian cancer. 42 Knockdown of E2F5-induced cell death via the TP53-dependent pathway in breast cancer cells carrying wild-type TP53. 41 E2F5, which was highly expressed in malignant tissues when compared to the nonmalignant tissues, promoted ovarian carcinogenesis by regulating Hippo and Wnt pathways.…”
Section: Discussionmentioning
confidence: 99%
“…As oncogenes, E2F family transcription factors play a core role in regulating cell proliferation ( Polager et al, 2002 ; Stevens and La Thangue, 2003 ; Fang and Han, 2006 ). E2F5 promotes the proliferation of hepatocellular ( Jiang et al, 2011 ), prostate ( Li et al, 2018 ), glioblastoma ( Fang et al, 2018 ), gastric ( Li et al, 2021 ), and ovarian ( Malgundkar et al, 2021 ) cancer cells. ChIP experiments have shown that E2F4/5·p107/p130 complexes contribute to the regulation of early cell-cycle expression, including G0/G1 transition ( Sardet et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…E2F5 belongs to the E2F transcription factor family which is involved in cell growth, apoptosis, differentiation and cell cycle in cancers [28]. Previous studies demonstrate that aberrant expression of E2F5 is associated with the malignancy of ovarian cancer, gastric cancer, lung cancer, and hepatocellular carcinoma [29][30][31][32]. Ping Zhou recently reported that identification of E2F transcription factor 7 as a novel potential biomarker for oral squamous cell carcinoma [33].…”
Section: Discussionmentioning
confidence: 99%